S EVERYDAY ENGLISH BERBASIS COMMUNICATIVE LANGUAGE TEACHING (CLT) UNTUK MENINGKATKAN KEPERCAYAAN DIRI DAN KEMAMPUAN KOMUNIKASI PERFORMER DI SAUNG ANGKLUNG UDJO - Sri Handayani; Kandagasari, Nanan; Fauzi, Deri Fikri; Dewi, Mutiara Indah Nirmala; Lingga, Thomson Radesman; Raditiyanto, Satria; Haryani, Heni (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2026)
This research was based on the Community Service Program activities in the program of Everyday English based on CLT held in the Saung Angkung Udjo tourist area. The purpose of this study was to describe the implementation of the program by observing the effectiveness of the CLT approach applied in order to improve the English communication skills of child performers. This study involved 30 performers aged 8–15 years who are active in angklung and Sundanese cultural arts performances. Observations and interviews were applied to gather data and information that support this research. The results of the activity showed that participants already have the basics of English, but still experience limitations in using the language communicatively. The results of the observation showed that after participating in the training, the performers showed better English skills and were more confident in conveying vocabulary in English to tourists. Thus, the Everyday English program based on CLT can be an applicable learning model in improving English communication competency in the context of cultural tourism in terms of improving the quality of interaction between artists and tourists. Keywords: Communicative Language Teaching, Everyday English, Communication Competence, Cultural Tourism, Performer